Modified method for isolation of langerhans islets from mice - Kopská, Tereza; Fürstová, Vlasta; Kovář, Jan (Transplantation proceedings, 2008)
Successful isolation of Langerhans islets is a crucial prerequisite for their experimental or possible clinical use such as transplantation. Centrifugation in a Ficoll gradient is a common step used for separation of Langerhans islets from exocrine tissue. However, islets have been reported to be negatively affected by employing Ficoll gradients. Therefore, the aim of this study was to modify the isolation procedure by excluding Ficoll gradient centrifugation to obtain a similar or better yield of viable, functional islets. In our modification of the isolation procedure, the separation of islets from exocrine tissue was based on their sedimentation rate combined with their differential ability to attach to the surface of culture dishes for suspension cells. The resulting purity of islets facilitated their handpicking from the suspension. The mean yield was 900 viable, insulin-producing islets per mouse, which was comparable to or even higher than the yield in commonly used protocols. Our modification of the isolation method may be useful when centrifugation in Ficoll gradient is undesirable due to potential toxicity.
Keywords: Islets of Langerhans; Cell Survival; myši inbrední ICR; Mice, Inbred ICR; Pancreas; Langerhansovy ostrůvky; ženské pohlaví; Mice, Inbred BALB C; myši; viabilita buněk; Cell Separation; buněčná adheze; Mice; Islets of Langerhans Transplantation; transplantace Langerhansových ostrůvků; Animals; zvířata; počet buněk; separace buněk; pankreas; Cell Adhesion; myši inbrední BALB C; Female; Cell Count